2017
DOI: 10.1016/j.ssi.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked perfluoropolyether solid electrolytes for lithium ion transport

Abstract: A B S T R A C TPerfluoropolyethers (PFPE) are commercially available non-flammable short chain polymeric liquids. Endfunctionalized PFPE chains solvate lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt and these mixtures can be used as electrolytes for lithium (Li) batteries. Here we synthesize and characterize a new class of solid PFPE electrolytes. The electrolytes are made by either thermal or UV crosslinking PFPE chains with urethane methacrylate end-groups. For the synthesis of thermally crosslinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 51 publications
(74 reference statements)
5
37
0
Order By: Relevance
“…VTF is closely relatedt ot he free volume model where there is ad istribution of voids through the polymer matrix broughta bout by polymer motion. The electrochemical window largely depends on the conductive salt used for the nanocomposite and density functional theory calculations performed by Pandiana nd colleagues [60] with PEO/Li-salt composites determined that the cathodica nd anodic limits were determined by the anion and monomer repeat units, respectively.S ubstitution of ethylene chainsw ith fluorine atoms resulted to an extended potential window and correlating to the satisfactory experimental results of Devauxa nd group, [61] development of perfluorinated SPEs may be the next step in the field of solid-statee lectrolytes. Use of this model to fit experimental data is only valid when there is only as ingle existingp hase and provided that the polymer is amorphous.…”
Section: Electrochemical Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…VTF is closely relatedt ot he free volume model where there is ad istribution of voids through the polymer matrix broughta bout by polymer motion. The electrochemical window largely depends on the conductive salt used for the nanocomposite and density functional theory calculations performed by Pandiana nd colleagues [60] with PEO/Li-salt composites determined that the cathodica nd anodic limits were determined by the anion and monomer repeat units, respectively.S ubstitution of ethylene chainsw ith fluorine atoms resulted to an extended potential window and correlating to the satisfactory experimental results of Devauxa nd group, [61] development of perfluorinated SPEs may be the next step in the field of solid-statee lectrolytes. Use of this model to fit experimental data is only valid when there is only as ingle existingp hase and provided that the polymer is amorphous.…”
Section: Electrochemical Propertiessupporting
confidence: 61%
“…The electrochemical window largely depends on the conductive salt used for the nanocomposite and density functional theory calculations performed by Pandian and colleagues with PEO/Li‐salt composites determined that the cathodic and anodic limits were determined by the anion and monomer repeat units, respectively. Substitution of ethylene chains with fluorine atoms resulted to an extended potential window and correlating to the satisfactory experimental results of Devaux and group, development of perfluorinated SPEs may be the next step in the field of solid‐state electrolytes.…”
Section: Ion Conductionmentioning
confidence: 99%
“…Using the data of the impedance test in the Li-MnO 2 system it was shown that the conductivity of the PVC-PC-LiClO 4 gel electrolyte is 5  10 -4 S/cm at room temperatures. This value is in excess of the conductivity for liquid (~3  10 -4 S/cm) [10,11] and solid (~10 -5 S/cm) [12,13] electrolytes. Singleparticle and collective dynamics of solvent molecules (PC and PC-LiClO 4 ) in free state and in the pores of polymer gels based on PVC in the ranges of observation times 10 -10 -10 -12 s were determined by quasi-elastic neutron scattering technique.…”
Section: Resultsmentioning
confidence: 85%
“…This prompts further research on solid PFPE-based electrolytes, as they are not limited in the anodic domain. Fluorinated solid PFPE/LiTFSI was synthesized with urethane methacrylate end-groups [278] but have not yet been tested as electrolytes. Finally, we note that the polymers and copolymers that compose the electrolytes that we have mentioned are linear.…”
Section: Polymer Electrolytesmentioning
confidence: 99%